       question about writing an expression in another way

• To: mathgroup at smc.vnet.net
• Subject: [mg128462] question about writing an expression in another way
• From: dimitris anagnostou <dimanag78 at gmail.com>
• Date: Mon, 22 Oct 2012 02:02:52 -0400 (EDT)
• Delivered-to: l-mathgroup@mail-archive0.wolfram.com
• Delivered-to: l-mathgroup@wolfram.com
• Delivered-to: mathgroup-newout@smc.vnet.net
• Delivered-to: mathgroup-newsend@smc.vnet.net

```Hello to all.
I have the following expression:

u1=-((c P =E2^2 (c =E2^2 + =ED))/(
=E3 =EC (-1 - 4 c^3 =E2^5 (=E2 - =E3) + c^2 (-6 =E2^4 + 4 =E2^3 =E3) +
2 c =E2^2 (-2 + =ED) + =ED))) - (
P (-2 c =E2^2 (-1 + =ED) + (-1 + =ED)^2 +
c^2 =E2^3 (-2 =E2 (-1 + =ED) + =E3 (-3 + 2 =ED))))/(
=E2 =EC (-1 - 4 c^3 =E2^5 (=E2 - =E3) + c^2 (-6 =E2^4 + 4 =E2^3 =E3) +
2 c =E2^2 (-2 + =ED) + =ED));

with

{=E3 -> Sqrt[1/c + =F1^2], =E2 -> =F1}

I know from external source that u1 is equal to

u2=(P (1 - =ED))/(=EC =F1) - (c P (1 - =ED) =F1)/(=EC (1 + c =F1^2)) - (
c P (1 - =ED) =F1 (-1 + =ED + c =E3 =F1 (1 - 2 c =E3 =F1 + 2 c =F1^2)))/(
=EC (4 c^3 =E2^3 =E3^3 - (1 + 2 c =E2^2) (1 + 2 c^2 =E2^2 =E3^2 - =ED)) (1 + c =F1^2)
);

Indeed,

Iu1 - u2 /. {=E3 -> Sqrt[1/c + =F1^2], =E2 -> =F1} // Together
0

How is possible to "force" Mathematica to write down u1 as u2?

Thank you very much, in advance.
Dimitris

```

• Prev by Date: Heat kernel on a mobius band in a closed form
• Next by Date: OutputResponse gives funny results
• Previous by thread: Heat kernel on a mobius band in a closed form
• Next by thread: OutputResponse gives funny results